1837 Ala. Laws 7 - (:unkn) unknown (My University, 1837)
Mandated that any person carrying a Bowie knife or Arkansas toothpick who cuts or stabs another, causing them to die, shall be adjudged as a crime of murder, with the offender having held malice aforethought.
Keywords: COMMITTING CRIME W/ WEAPON - NON-GUN ARMS